PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBASIS MEDIA INTERAKTIF QUIZZIZ DAN MEDIA KONKRET DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS V : Penelitian Tindakan Kelas (PTK) - Friska Widyastuti; Nuraedah Nuraedah; Siti Rahma (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the use of the Problem Based Learning (PBL) model integrated with Quizziz and concrete media in improving learning motivation of fifth-grade students at SDN 22 Palu. The research method employed was Classroom Action Research (CAR) based on the Kemmis and McTaggart model carried out in two cycles. Data collection techniques included observation, learning motivation questionnaires, and documentation. The findings reveal that the implementation of PBL combined with Quizziz significantly enhanced students’ motivation. Students became more enthusiastic and actively engaged in group discussions and interactive quizzes. Intrinsic motivation was fostered by curiosity and satisfaction in finding solutions, while extrinsic motivation was encouraged through a point system. In conclusion, integrating PBL with interactive Quizziz , and concrete media proved effective in creating an enjoyable learning environment that boosts students’ motivation in elementary school.